Hydrophilic modified microporous membrane, composite ion exchange membrane and application thereof
The hydrophilic modified microporous membrane is formed on the microporous membrane through spray coating technology, which solves the problem of insufficient hydrophilicity of the microporous membrane, improves the performance and stability of the ion exchange membrane, and achieves better structure and performance Combined.
Patent Information
- Application Number
- CN202411470816.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-03
AI Technical Summary
In the application of existing microporous membranes, there are low surface energy and poor hydrophilicity, which leads to poor structural deformation and recombination effects, affecting the performance of the ion exchange membrane.
Spray coating technology is used to coat hydrophilic polymers on the surface of microporous membranes to improve their hydrophilicity, form hydrophilic modified microporous membranes, enhance the binding force with ion exchange resins, and improve electrochemical and mechanical properties. .
On the basis of maintaining the original microporous membrane structure, it significantly improves hydrophilicity, reduces processing difficulty, enhances the mechanical strength, dimensional stability, barrier properties and transmission properties of the ion exchange membrane, and extends its service life.
Smart Images

Figure CN119236699A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, and in particular to a hydrophilic modified microporous membrane, a composite ion exchange membrane and applications thereof. Background Art
[0002] Microporous membranes are widely used in the fields of medicine, construction, water treatment, air purification, membrane reactors, battery separators and food packaging due to their unique structure and performance. With the increasing requirements for the thickness and strength of ion exchange membranes in various fields, microporous membranes with high porosity and high strength are used as the reinforcement layer of ion exchange membranes in composite ion exchange membranes to meet the requirements of thickness and strength. However, the microporous membranes currently used in ion exchange membranes have shortcomings such as low surface energy and poor hydrophilicity. Therefore, the development of a reinforcement layer that is more suitable for ion exchange membranes is an important research direction for microporous membranes.
[0003] Microporous membranes based on organic polymers are the most widely used type of microporous membranes with the largest current output. The matrix materials of such microporous membranes are also called skeleton polymer materials. For the microporous membranes required for the reinforcement layer of ion exchange membranes, the current research direction is mainly to improve their mechanical strength, pore size distribution uniformity, and improve the surface energy of the microporous membrane to improve the hydrophilicity of the microporous membrane.
[0004] The surface modification of microporous membrane by polymer coating is to directly attach the modified polymer material to the microporous membrane to form a thin layer. The operation is simple, with few steps and easy to produce continuously. The commonly used coating methods for surface modification of microporous membranes for ion exchange membranes include blade coating, slit coating and dip coating. These three coating methods are to compound the continuous polymer dispersion fluid with the microporous membrane. The mechanical force on the microporous membrane during the compounding process is small, but the dispersion usually needs to completely infiltrate the microporous membrane. The structure of the microporous membrane is greatly affected by the solvent. The microporous membrane will undergo significant changes in thickness, pore size and porosity under the action of the polymer dispersion solvent. This structural change may be unfavorable for the composite preparation of high-performance ion exchange membranes by ion exchange resins and microporous membranes, affecting subsequent applications.
[0005] For other coating methods, such as roller coating, extrusion coating and micro-concave transfer coating, not only the solvent affects the microporous membrane structure, but also a large mechanical force perpendicular to the membrane surface will be generated during the processing. This mechanical force can improve the composite effect, but it will also drastically change the structure of the microporous membrane and is not suitable for surface modification of the microporous membrane. Air knife coating uses high-pressure gas to spray the polymer material evenly on the substrate through the nozzle in the coating head to form a thin and uniform coating. The polymer material dispersion is torn into small-sized droplets by the high-pressure gas and coated on the microporous membrane. The deformation effect of the solvent on the microporous membrane is reduced, but the mechanical force of the high-pressure gas on the microporous membrane will still cause serious deformation of the microporous membrane structure. Summary of the invention
[0006] The present invention is based on the inventor's discovery and understanding of the following facts and problems: the microporous membrane currently used in ion exchange membranes has the disadvantages of low surface energy and poor hydrophilicity. The surface modification of the microporous membrane by coating the polymer material on the surface of the microporous membrane by blade coating, slit coating, dip coating, etc. will cause the deformation of the microporous structure of the microporous membrane, affecting subsequent applications.
[0007] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the embodiments of the present invention provide a hydrophilic modified microporous membrane, a composite ion exchange membrane and its application, wherein the hydrophilic polymer is spray-coated on the surface of the microporous membrane, which has little effect on the porosity, pore size and other structures of the microporous membrane, and can improve the surface hydrophilicity of the microporous membrane while maintaining the original microporous membrane structure; the basic groups or phosphonic acid groups on the surface of the hydrophilic modified microporous membrane can form ionic crosslinking with the acidic groups of the ion exchange resin, thereby improving the binding effect between the ion exchange resin and the surface of the microporous membrane, and improving the electrochemical performance, barrier properties, dimensional stability and durability of the composite ion exchange membrane.
[0008] An embodiment of the present invention provides a hydrophilic modified microporous membrane, comprising a microporous membrane and a hydrophilic polymer, wherein the hydrophilic polymer is spray-coated on one or both sides of the microporous membrane, and the hydrophilic polymer comprises a cation exchange polymer and / or an anion exchange polymer.
[0009] Advantages and technical effects of the hydrophilic modified microporous membrane of the embodiment of the present invention: the hydrophilic polymer is spray-coated on the surface of the microporous membrane. Compared with microporous membranes with other coating methods, the hydrophilic polymer has less influence on the porosity, pore size and other structures of the microporous membrane, and can improve the hydrophilicity of the microporous membrane while maintaining the original microporous membrane structure. When the microporous membrane is applied to an ion exchange membrane, the improvement of the hydrophilicity can improve the wettability of the microporous membrane and the ion exchange resin dispersion during the composite process, and reduce the processing difficulty of the ion exchange membrane; the improvement of the hydrophilicity can improve the filling property after composite molding, and improve the mechanical strength, dimensional stability, barrier and ion transmission performance of the ion exchange membrane.
[0010] In the embodiment of the present invention, the hydrophilic polymer includes a cation exchange polymer and / or an anion exchange polymer, which can improve the surface hydrophilicity of the microporous membrane. When the ionic group of the hydrophilic polymer can be used as a basic group, the ionic group on the surface of the obtained hydrophilic modified microporous membrane can be used as a basic group to form an ionic crosslinking effect with the acidic group of the ion exchange resin. This strongest physical crosslinking effect can improve the binding effect between the ion exchange resin and the surface of the microporous membrane, and enhance the dimensional stability and durability of the ion exchange membrane. When the hydrophilic polymer contains a phosphonic acid group, the phosphonic acid group of the hydrophilic modified microporous membrane can play a proton compensation role, and form multiple ion transmission channels with the acidic group of the ion exchange resin, reduce the ion transmission energy barrier, and can also be used as a Lewis base to form an ionic crosslinking structure with the acidic group of the ion exchange resin, improve the binding effect between the ion exchange resin and the surface of the microporous membrane, and improve the mechanical properties, chemical stability and barrier properties of the ion exchange membrane.
[0011] In some embodiments, the hydrophilic polymer includes at least one of a nitrogen onium ion functionalized resin, a phosphonated vinyl polymer, a perfluorophosphonic acid resin, and a perfluorosulfonimide resin;
[0012] and / or, the microporous membrane comprises at least one of a fluorine-containing olefin polymer, a non-fluorine-containing olefin polymer, and an aromatic polymer;
[0013] and / or, the mass ratio of the microporous membrane to the hydrophilic polymer is 100:0.01-25;
[0014] and / or, the thickness of the hydrophilic modified microporous membrane is 1 μm to 1 mm;
[0015] and / or, the average pore size of the hydrophilic modified microporous membrane is 0.01 μm to 1 μm;
[0016] And / or, the porosity of the hydrophilic modified microporous membrane is 30% to 95%.
[0017] The present invention provides a method for preparing a hydrophilic modified microporous membrane, comprising the following steps:
[0018] (1) dispersing a hydrophilic polymer in a solvent to form a dispersion;
[0019] (2) The dispersion is spray-coated on one or both sides of a microporous membrane, and then heat-treated to obtain a hydrophilically modified microporous membrane.
[0020] In the embodiment of the present invention, the dispersion of the hydrophilic polymer is spray-coated on the surface of the microporous membrane, the hydrophilic polymer dispersion is broken into micro-nano-scale mist droplets from a continuous fluid in the spray device, and then coated on the surface of the microporous membrane, and the hydrophilic modified microporous membrane is obtained after heat treatment to remove the solvent, and the surface of the hydrophilic modified microporous membrane is coated with the hydrophilic polymer, that is, the hydrophilic polymer is loaded on the membrane surface and / or pores and / or fiber structure surface of the microporous membrane as a hydrophilic coating, so as to improve the surface hydrophilicity of the microporous membrane. The surface modification of the microporous membrane by the spray coating method has high coating accuracy, good coating effect, wide application range, simple operation, and meets the needs of industrial continuous production.
[0021] In the embodiment of the present invention, the microporous membrane is surface-modified by coating, and the volume of fluid to be coated is as small as possible to reduce the effect of the solvent on the microporous membrane structure. The microporous membrane is also required to be subjected to as little mechanical force as possible to reduce the deformation of the microporous membrane caused by mechanical force. Compared with processing methods such as blade coating, slit coating and dip coating, spray coating requires less solvent and can reduce the effect of the solvent on the microporous membrane structure; compared with processing methods such as roller coating, extrusion coating and micro-concave transfer coating, spray coating does not require a large amount of solvent to immerse the microporous membrane, and the coating device will not directly contact the microporous membrane and be subjected to mechanical force. Spray coating can evenly coat the hydrophilic polymer on the surface of the microporous membrane to form a coating. The particle size of the mist-like gel particles formed by the hydrophilic polymer and the solvent can reach less than 1μm, so that the coating of the hydrophilic polymer on the surface of the microporous membrane is thinner and has less effect on the porosity and pore size. The mechanical force of spray coating on the microporous membrane is negligible, and the small amount of solvent has little effect on the structure of the microporous membrane. It can improve the hydrophilicity of the microporous membrane while maintaining the original microporous membrane structure.
[0022] In some embodiments, in step (1), the mass percentage concentration of the dispersion is 0.01% to 60%;
[0023] And / or, in step (2), the spray coating nozzle includes at least one of a pressure nozzle, a rotary nozzle, a two-phase flow nozzle, an ultrasonic nozzle, and an electrostatic nozzle;
[0024] And / or, in step (2), the temperature of the heat treatment is room temperature to 300°C.
[0025] In some embodiments, the spray coating uses an ultrasonic nozzle; preferably, the frequency of the ultrasonic nozzle is 0.2 MHz to 10 MHz;
[0026] and / or, the liquid transmission rate of a single nozzle of the spray coating is ≤50 mL / s;
[0027] and / or, the average particle size of the atomized droplets of the spray coating is ≤50 μm;
[0028] And / or, the spray coating has a spray distance of 1 cm to 150 cm.
[0029] The embodiment of the present invention provides a composite ion exchange membrane, comprising an ion exchange resin and a hydrophilic modified microporous membrane, wherein the hydrophilic modified microporous membrane comprises the hydrophilic modified microporous membrane described in the embodiment of the present invention or the hydrophilic modified microporous membrane prepared by the preparation method described in the embodiment of the present invention.
[0030] In an embodiment of the present invention, a hydrophilic modified microporous membrane is used as a reinforcing layer and composited with an ion exchange resin to prepare a composite ion exchange membrane. The hydrophilic polymer dispersion is spray-coated on the surface of the microporous membrane, thereby improving the hydrophilicity of the microporous membrane and the filling property of the ion exchange resin in the hydrophilic modified microporous membrane. The basic groups or phosphonic acid groups in the hydrophilic polymer can form ionic crosslinks with the acidic groups of the ion exchange resin, thereby improving the degree of bonding between the ion exchange resin and the hydrophilic modified microporous membrane interface, thereby achieving improvements in the electrochemical properties, mechanical properties, barrier properties and durability of the composite ion exchange membrane. When the composite ion exchange membrane is a proton exchange membrane, the improvement in the hydrophilicity of the microporous membrane can also improve the water retention of the proton exchange membrane, thereby broadening the operating temperature of the proton exchange membrane.
[0031] In some embodiments, the ion exchange resin is loaded on one or both sides of the hydrophilic modified microporous membrane;
[0032] And / or, the thickness of the composite ion exchange membrane is 3 μm to 500 μm;
[0033] and / or, the ion exchange capacity of the composite ion exchange membrane is 0.1 mmol / g to 5.2 mmol / g;
[0034] And / or, the ion exchange resin includes at least one of perfluorosulfonic acid resin, perfluorosulfonimide resin, polyacid side chain perfluoro resin, sulfonated polytrifluorostyrene, sulfonated polysulfone, sulfonated polyethersulfone, sulfonated polyetheretherketone, sulfonated polyaryletherketone, sulfonated polyarylethernitrile, sulfonated polyphosphazene, sulfonated polyphenylene oxide, sulfonated polybenzonitrile, sulfonated polyimide or sulfonated polybenzimidazole.
[0035] The present invention provides a method for preparing a composite ion exchange membrane, comprising the following steps:
[0036] 1) dispersing an ion exchange resin in a solvent to obtain an ion exchange resin dispersion;
[0037] 2) coating the ion exchange membrane resin dispersion on one side or both sides of the hydrophilic modified microporous membrane and drying to obtain a composite ion exchange membrane.
[0038] The embodiment of the present invention provides an application of a hydrophilic modified microporous membrane or a composite ion exchange membrane for at least one of filtration, separation, sealing material, and textile material.
[0039] In some embodiments, the invention is used in at least one of fuel cells, water electrolysis, flow batteries, chlor-alkali industry, electrodialysis, or osmosis. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 are the surface SEM images of MF-3A and e-PTFE-3.
[0041] Figure 2 are the contact angle images of the unmodified microporous membrane and the hydrophilically modified microporous membrane.
[0042] Figure 3 are contact angle images of MF-1B, D-MF-1B, and D-MF-1E.
[0043] Figure 4 are cross-sectional SEM images of PEM-1B and D-PEM-1.
[0044] Figure 5 These are the polarization curves of PEM-1B, D-PEM-1, and D-PEM-1B.
[0045] Figure 6 is the flow battery efficiency of PEM-4 and D-PEM-4A. DETAILED DESCRIPTION
[0046] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0047] A hydrophilic modified microporous membrane according to an embodiment of the present invention comprises a microporous membrane and a hydrophilic polymer, wherein the hydrophilic polymer is spray-coated on one or both sides of the microporous membrane, and the hydrophilic polymer comprises a cation exchange polymer and / or an anion exchange polymer.
[0048] The hydrophilic modified microporous membrane of the embodiment of the present invention has a hydrophilic polymer coated on the surface of the microporous membrane by spraying. Compared with microporous membranes with other coating methods, the microporous membrane has less influence on the porosity, pore size and other structures, and can improve the hydrophilicity of the microporous membrane while maintaining the original microporous membrane structure. When the microporous membrane is applied to an ion exchange membrane, the improvement of the hydrophilicity can improve the wettability of the microporous membrane and the ion exchange resin dispersion during the composite process, and reduce the processing difficulty of the ion exchange membrane; the improvement of the hydrophilicity can improve the filling property after composite molding, and improve the mechanical strength, dimensional stability, barrier property and ion transmission performance of the ion exchange membrane.
[0049] In the embodiment of the present invention, the hydrophilic polymer includes a cation exchange polymer and / or an anion exchange polymer, which can improve the surface hydrophilicity of the microporous membrane. When the ionic group of the hydrophilic polymer can be used as a basic group, the ionic group on the surface of the obtained hydrophilic modified microporous membrane can be used as a basic group to form an ionic crosslinking effect with the acidic group of the ion exchange resin. This strongest physical crosslinking effect can improve the binding effect between the ion exchange resin and the surface of the microporous membrane, and enhance the dimensional stability and durability of the ion exchange membrane. When the hydrophilic polymer contains a phosphonic acid group, the phosphonic acid group of the hydrophilic modified microporous membrane can play a proton compensation role, and form multiple ion transmission channels with the acidic group of the ion exchange resin, reduce the ion transmission energy barrier, and can also be used as a Lewis base to form an ionic crosslinking structure with the acidic group of the ion exchange resin, improve the binding effect between the ion exchange resin and the surface of the microporous membrane, and improve the mechanical properties, chemical stability and barrier properties of the ion exchange membrane.
[0050] In some embodiments, the hydrophilic polymer comprises a cation exchange polymer and / or an anion exchange polymer; optionally, the anion exchange polymer comprises a nitrogen onium ion functionalized resin; the cation exchange polymer comprises at least one of a perfluorosulfonyl imide resin, a phosphonated vinyl polymer, and a perfluorophosphonic acid resin;
[0051] Optionally, the hydrophilic polymer includes at least one of a nitrogen onium ion functionalized resin, a phosphonated vinyl polymer, a perfluorophosphonic acid resin, and a perfluorosulfonyl imide resin; Optionally, the nitrogen onium ion functionalized resin includes a perfluoro nitrogen onium ion resin; the phosphonated vinyl polymer includes at least one of a phosphonated polyvinyl alcohol and a phosphonated ethylene-vinyl alcohol copolymer;
[0052] Preferably, the hydrophilic polymer includes at least one of perfluoronitrogenium ion resin, phosphonated polyvinyl alcohol, and phosphonated ethylene-vinyl alcohol copolymer; more preferably, the hydrophilic polymer includes at least one of perfluoronitrogenium ion resin and phosphonated ethylene-vinyl alcohol copolymer.
[0053] In the embodiment of the present invention, by selecting the type of hydrophilic polymer, it is beneficial to further improve the hydrophilicity, mechanical properties, electrochemical properties and processability of the microporous membrane. The hydrophilic polymer includes a cation exchange polymer and / or an anion exchange polymer. When applied to an ion exchange membrane, the basic group or phosphonic acid group on the surface of the microporous membrane forms an ionic crosslinking effect with the acidic group of the ion exchange resin. This strongest physical crosslinking effect can improve the binding effect between the ion exchange resin and the surface of the microporous membrane, and enhance the dimensional stability and durability of the ion exchange membrane. When the hydrophilic polymer contains a phosphonic acid group, the phosphonic acid group of the hydrophilically modified microporous membrane can play a proton compensation role, and form multiple ion transmission channels with the acidic group of the ion exchange resin, reducing the ion transmission energy barrier. The sulfonimide group in the perfluorosulfonyl imide resin is different from the sulfonic acid group, which can improve the proton transmission capacity under high temperature and low humidity conditions.
[0054] In some embodiments, the general formula of the perfluoronitrogen onium ion resin is as shown in formula (1):
[0055]
[0056] Wherein, a is an integer of 0 to 6, b is an integer of 2 to 5, and e is an integer of 0 to 1; R 1 Selected from C 1 ~C 20 Alkyl; R 2 Selected from C 1 ~C 20 An alkylene group; Q is a nitrogen onium ion group;
[0057] There is no particular restriction on the type of the nitrogen onium ion group; optionally, the nitrogen onium ion group is selected from at least one of the following structural formulas:
[0058]
[0059] Among them, R 3 ~R 25 Each independently selected from H, C 1 ~C 20 Alkyl or C 6 ~C 20 Aryl, X - Selected from OH - Or halide ions; optionally, the halide ions include at least one of fluoride ions, chloride ions, bromide ions, and iodide ions;
[0060] Optionally, the perfluoronitrogen onium ion resin is composed of tetrafluoroethylene repeating units and perfluorovinyl ether repeating units. When the structure of the perfluorovinyl ether repeating unit is determined, the ion exchange equivalent (EW) of the resin is determined by x, and the value of EW is the molecular weight of the tetrafluoroethylene repeating unit multiplied by x plus the molecular weight of the perfluorovinyl ether repeating unit; y determines the molecular weight of the perfluoronitrogen onium ion resin;
[0061] Optionally, the perfluoronitrogen onium ion resin can be combined with different anions; optionally, the anions include at least one of halide ions and hydroxide ions; specifically, the halide ions include at least one of fluoride ions, chloride ions, bromide ions, and iodide ions;
[0062] Optionally, the EW of the perfluoronitrogen onium ion resin is 400-5000 g / mol, preferably 500-2000 g / mol, more preferably 600-1200 g / mol; the number average molecular weight (Mn) of the perfluoronitrogen onium ion resin is 30000-3000000, preferably 60000-1500000, more preferably 70000-800000.
[0063] In the embodiments of the present invention, the hydrophilicity, mechanical properties, electrochemical properties and processability of the microporous membrane are further improved by preferably using a perfluoronitrogen onium ion resin. For example, relatively speaking, when the EW of the perfluoronitrogen onium ion resin is too low, the hydrophilicity of the material is relatively too strong, and it is easy to dissolve during the use of the microporous membrane, causing mass loss. When the EW is too high, the hydrophilicity decreases, and the dissolution process is relatively difficult, and the effect of improving the hydrophilicity of the microporous membrane material is limited. The molecular weight of the perfluoronitrogen onium ion resin is too low, and the stability and mechanical properties of the material are relatively low, making it difficult to process and shape, while high molecular weight materials are difficult to prepare and difficult to dissolve and process.
[0064] In some embodiments, the general structural formula of the phosphonated ethylene-vinyl alcohol copolymer (phosphonated EVOH) is as shown in formula (2):
[0065]
[0066] Optionally, w is 18 to 27000; z is 227 to 22700; y is 0 to 3500;
[0067] In formula (2), the vinyl repeating unit A 1 , vinyl alcohol repeating unit A 2 , vinyl acetate repeating unit A 3 and Among them, the name A is the repeating unit 4 ;
[0068] Optionally, define repeating unit A 4The molar content is the phosphonation degree of the phosphonated EVOH, in which the repeating unit A 4 The molar content (u / (w+z+y)) is 0.1% to 80%, specifically, for example, 0.1%, 0.5%, 1%, 10%, 20%, 50%, 80%, preferably, 0.5% to 50%;
[0069] Optionally, in the phosphonated EVOH, the repeating unit A 1 The molar content (w / (w+z+y)) is 25% to 50%; the repeating unit A 2 The molar content ((zu) / (w+z+y)) is 10% to 75%; the repeating unit A 3 The molar content (y / (w+z+y)) is 0 to 0.7%; the repeating unit A 4 The molar content (u / (w+z+y)) is 0.1% to 80%, preferably 0.5% to 50%;
[0070] Optionally, the phosphonated ethylene-vinyl alcohol copolymer is combined with different cations; optionally, the cations include at least one of hydrogen ions, monovalent metal cations, ammonium ions, alkaline earth metal ions, manganese ions or cerium ions; optionally, the monovalent metal cations include at least one of lithium ions, sodium ions, potassium ions, silver ions; the alkaline earth metal ions include at least one of magnesium ions and calcium ions.
[0071] In the embodiment of the present invention, by preferably phosphonating ethylene-vinyl alcohol copolymer, the hydrophilicity, mechanical properties, electrochemical properties and processability of the microporous membrane are further improved. When the hydrophilic polymer contains phosphonic acid groups, the phosphonic acid groups can play a proton compensation role and form multiple ion transmission channels with the acidic groups of the ion exchange resin to reduce the ion transmission energy barrier. It can also serve as a Lewis base to form an ion cross-linked structure with the acidic groups of the ion exchange resin, thereby improving the binding effect between the ion exchange resin and the surface of the microporous membrane and improving the mechanical properties, chemical stability and barrier properties of the ion exchange membrane.
[0072] In some embodiments, the microporous membrane comprises at least one of a fluorine-containing olefin polymer, a non-fluorine-containing olefin polymer, and an aromatic polymer; the microporous membrane comprises a skeleton polymer material; the skeleton polymer material comprises at least one of a fluorine-containing olefin polymer, a non-fluorine-containing olefin polymer, and an aromatic polymer;
[0073] Optionally, the fluorine-containing olefin polymer includes at least one of polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene-ethylene copolymer, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer (THV), polyvinyl fluoride (PVF), polychlorotrifluoroethylene (PCTFE), and ethylene-chlorotrifluoroethylene copolymer (ECTFE);
[0074] Optionally, the non-fluorinated olefin polymer includes at least one of polyethylene, polypropylene, ethylene-propylene copolymer, and ethylene-1-octene copolymer;
[0075] Optionally, the aromatic polymer includes at least one of polyarylether polymers, polysulfone polymers, polybenzimidazole polymers, polyimide polymers, polybenzonitrile polymers or polyarylethernitrile polymers;
[0076] Preferably, the skeleton polymer material includes at least one of PTFE, FEP, ETFE, PVDF, PVF, PFA, ECTFE, polyethylene, polypropylene, polyaryletherketone, polysulfone, polyethersulfone, polyethersulfoneketone, polybenzimidazole, polyimide or polyetheretherketone; further preferably, it includes at least one of PTFE, ETFE, polyethylene or polyetheretherketone; more preferably, PTFE.
[0077] In the embodiment of the present invention, among the skeleton polymer materials, the chemical stability of the fluorinated olefin polymer is better than that of the non-fluorinated olefin polymer and the aromatic polymer, and the good chemical stability can ensure the service life of the ion exchange membrane and its components. PTFE has the best chemical stability, and the microporous membrane prepared has high strength, and is the most preferred skeleton polymer material.
[0078] In some embodiments, the microporous membrane comprises at least one of a hollow fiber membrane, a tubular membrane, or a flat membrane layer structure, preferably a flat membrane layer structure.
[0079] In some embodiments, the preparation method of the microporous membrane includes at least one of nuclear track etching, micro-nano processing, stretching, dissolution, sintering, phase inversion, membrane splitting or electrospinning. Optionally, the phase inversion method includes at least one of solvent evaporation, water vapor inhalation, thermally induced phase separation and non-solvent phase separation. Considering the production cost, production efficiency and continuous production capacity, preferably, the preparation method of the microporous membrane includes at least one of stretching, dissolution or phase inversion.
[0080] In some embodiments, the hydrophilic modified microporous membrane comprises a microporous membrane and a hydrophilic polymer, and the mass ratio of the microporous membrane (skeleton polymer material) to the hydrophilic polymer is 100:0.01 to 25, preferably, 100:0.1 to 15, further preferably, 100:0.1 to 10, and more preferably, 100:0.1 to 5. In the embodiment of the present invention, the mass ratio of the microporous membrane to the hydrophilic polymer is 100:0.01 to 25, and the hydrophilic microporous membrane can maintain a good pore structure while improving the hydrophilicity, which is convenient for the filling and compounding of the ion exchange resin.
[0081] In some embodiments, the thickness of the microporous membrane is 1 μm to 1 mm, specifically, for example, 1 μm, 2 μm, 3 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 25 μm, 50 μm, 100 μm, 150 μm, 200 μm, 300 μm, 1 mm, preferably, 2 μm to 300 μm, further preferably, 3 μm to 200 μm, more preferably, 3 μm to 150 μm.
[0082] In some embodiments, the thickness of the hydrophilic modified microporous membrane is 1 μm to 1 mm, specifically, for example, 1 μm, 2 μm, 3 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 25 μm, 50 μm, 100 μm, 150 μm, 200 μm, 300 μm, 1 mm, preferably, 2 μm to 300 μm, further preferably, 3 μm to 200 μm, more preferably, 3 μm to 150 μm.
[0083] In some embodiments, the average pore size of the hydrophilic modified microporous membrane is 0.01 μm to 1 μm, preferably 0.03 μm to 0.7 μm, and more preferably 0.05 μm to 0.5 μm.
[0084] In some embodiments, the porosity of the hydrophilic modified microporous membrane is 30% to 95%, preferably 40% to 90%, more preferably 45% to 90%, and more preferably 50% to 90%.
[0085] In some embodiments, one side or both sides of the film are one side or both sides of the film along the thickness direction thereof.
[0086] A method for preparing a hydrophilic modified microporous membrane according to an embodiment of the present invention comprises the following steps:
[0087] (1) dispersing a hydrophilic polymer in a solvent to form a dispersion;
[0088] (2) The dispersion is spray-coated on one or both sides of a microporous membrane, and then heat-treated to obtain a hydrophilically modified microporous membrane.
[0089] In the embodiment of the present invention, the dispersion of the hydrophilic polymer is spray-coated on the surface of the microporous membrane, the hydrophilic polymer dispersion is broken into micro-nano-scale mist droplets from a continuous fluid in the spray device, and then coated on the surface of the microporous membrane, and the hydrophilic modified microporous membrane is obtained after heat treatment to remove the solvent, and the surface of the hydrophilic modified microporous membrane is coated with the hydrophilic polymer, that is, the hydrophilic polymer is loaded on the membrane surface and / or pores and / or fiber structure surface of the microporous membrane as a hydrophilic coating, so as to improve the surface hydrophilicity of the microporous membrane. The surface modification of the microporous membrane by the spray coating method has high coating accuracy, good coating effect, wide application range, simple operation, and meets the needs of industrial continuous production.
[0090] In the embodiment of the present invention, the microporous membrane is surface-modified by coating, and the volume of fluid to be coated is as small as possible to reduce the effect of the solvent on the microporous membrane structure. The microporous membrane is also required to be subjected to as little mechanical force as possible to reduce the deformation of the microporous membrane caused by mechanical force. Compared with processing methods such as blade coating, slit coating and dip coating, spray coating requires less solvent and can reduce the effect of the solvent on the microporous membrane structure; compared with processing methods such as roller coating, extrusion coating and micro-concave transfer coating, spray coating does not require a large amount of solvent to immerse the microporous membrane, and the coating device will not directly contact the microporous membrane and be subjected to mechanical force. Spray coating can evenly coat the hydrophilic polymer on the surface of the microporous membrane to form a coating. The particle size of the mist-like gel particles formed by the hydrophilic polymer and the solvent can reach less than 1μm, so that the coating of the hydrophilic polymer on the surface of the microporous membrane is thinner and has less effect on the porosity and pore size. The mechanical force of spray coating on the microporous membrane is negligible, and the small amount of solvent has little effect on the structure of the microporous membrane. It can improve the hydrophilicity of the microporous membrane while maintaining the original microporous membrane structure.
[0091] In some embodiments, in the step (1), the hydrophilic polymer is dispersed in a solvent to form a dispersion; alternatively, the hydrophilic polymer is dissolved in a solvent to form a dispersion; alternatively, the solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, tetramethyl sulfoxide, N-methylpyrrolidone, tetrahydrofuran, water, methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol; preferably, the solvent includes at least one of tetrahydrofuran, water, methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol; more preferably, the solvent includes at least one of water, ethanol, n-propanol, and isopropanol. In the embodiment of the present invention, the preferred solvent has a low boiling point, low toxicity, low pollution, and good effect of dispersing the hydrophilic polymer.
[0092] In some embodiments, in step (1), the mass percentage concentration of the dispersion is 0.01% to 60%, preferably 0.1% to 30%, and more preferably 0.1% to 25%. In the embodiment of the present invention, the mass percentage concentration of the dispersion is 0.01% to 60%, and a suitable concentration of the hydrophilic polymer dispersion is conducive to reducing costs. Too low a concentration of the hydrophilic polymer dispersion will result in a large amount of solvent required for coating, and too high a concentration will result in a thicker hydrophilic polymer coating.
[0093] In some embodiments, in step (2), the hydrophilic modified microporous membrane comprises a microporous membrane and a hydrophilic polymer, and the mass ratio of the microporous membrane (skeleton polymer material) to the hydrophilic polymer is 100:0.01-25, preferably, 100:0.1-15, further preferably, 100:0.1-10, and more preferably, 100:0.1-5. In the embodiment of the present invention, the mass ratio of the microporous membrane to the hydrophilic polymer is 100:0.01-25, and the hydrophilic microporous membrane can maintain a good pore structure while improving the hydrophilicity, which is convenient for the filling and compounding of the ion exchange resin.
[0094] In some embodiments, in step (2), the spray coating nozzle includes at least one of a pressure nozzle, a rotary nozzle, a two-phase flow nozzle, an ultrasonic nozzle, and an electrostatic nozzle; preferably, the spray coating nozzle includes at least one of an ultrasonic nozzle or an electrostatic nozzle; more preferably, an ultrasonic nozzle. According to the conventional definition in the field of spraying, the spraying technology using an ultrasonic nozzle is called ultrasonic spraying, and the spraying technology using an electrostatic nozzle is called electrostatic spraying.
[0095] In the embodiment of the present invention, compared with other nozzles, electrostatic spray and ultrasonic spray have high atomization quality, small atomized droplet size and are independent of fluid pressure. In electrostatic spray technology, the size of atomized droplets depends on the loading voltage, the electrode and the physical and chemical properties of the fluid. The higher the voltage, the better the atomization quality. Ultrasonic spray can obtain excellent atomization quality at a low liquid transmission rate, with a small and uniform droplet size and a minimum particle size of less than 1 μm. Other spray methods are relatively dependent on high liquid transmission rates and have larger droplet sizes.
[0096] In some embodiments, in step (2), the spray coating adopts ultrasonic spray; the spray coating adopts ultrasonic nozzle; optionally, the frequency of the ultrasonic spray (nozzle) is 0.2MHz to 10MHz, preferably, 0.4MHz to 5MHz, more preferably, 0.5MHz to 3MHz. In the embodiment of the present invention, the higher the frequency, the better the atomization quality and the smaller the particle size, but the equipment requirements are high, the equipment is easily damaged, and excessive volatilization of droplets may occur. The atomization equipment with a frequency of 0.5kHz to 3MHz has controllable cost and good atomization quality, and can prepare high-performance hydrophilic modified microporous membranes.
[0097] In some embodiments, the liquid transmission rate of a single nozzle of the spray coating is ≤50 mL / s; alternatively, the liquid transmission rate of a single ultrasonic nozzle is ≤50 mL / s, preferably, ≤10 mL / s, and more preferably, ≤3 mL / s. In the embodiment of the present invention, too high a liquid transmission rate of ultrasonic spraying will lead to a decrease in atomization quality, and preferably the liquid transmission rate of a single ultrasonic nozzle is ≤50 mL / s.
[0098] In some embodiments, the average particle size of the atomized droplets of the spray coating is ≤50 μm, preferably, ≤25 μm, and more preferably, ≤5 μm.
[0099] In some embodiments, the spray distance of the spray coating (the distance between the nozzle and the microporous membrane) is 1 cm to 150 cm; for the ultrasonic nozzle, that is, the distance between the ultrasonic nozzle and the microporous membrane is 1 cm to 150 cm, preferably, 5 cm to 100 cm, and more preferably, 10 cm to 80 cm. In the embodiment of the present invention, the spray distance of the ultrasonic nozzle can reach more than 5 m, but in the embodiment of the present invention, the preferred spray distance is 1 cm to 150 cm, because a spray distance that is too far will cause the droplets to dry excessively or even become solid particles, and a spray distance that is too close will cause the spraying area of a single nozzle to be too small, the spray efficiency is low, the loss is large, and the cost is high.
[0100] In some embodiments, the spray coating is vertical spray coating.
[0101] In some embodiments, in step (2), the temperature of the heat treatment is room temperature to 300°C, specifically, for example, 25°C, 30°C, 50°C, 100°C, 150°C, 160°C, 200°C, 300°C, preferably, room temperature to 200°C, more preferably, room temperature to 160°C; the time of the heat treatment is 0.5min to 30min, preferably, 1min to 15min, more preferably, 1min to 10min. In the embodiment of the present invention, the hydrophilic modified microporous membrane is obtained after the solvent is removed by heat treatment, and the spray-coated microporous membrane is very easy to dry, which is determined by the easy volatility of the solvent, the small amount of solvent and the uniform dispersion of the droplets, so it can be heat-treated and fixed at a lower temperature and in a shorter time. Excessive heat treatment temperature and heat treatment time not only consume a lot of energy, but also may cause aging or decomposition of the polymer material.
[0102] A composite ion exchange membrane according to an embodiment of the present invention comprises an ion exchange resin and a hydrophilic modified microporous membrane, wherein the hydrophilic modified microporous membrane comprises the hydrophilic modified microporous membrane according to the embodiment of the present invention or the hydrophilic modified microporous membrane prepared by the preparation method according to the embodiment of the present invention.
[0103] In an embodiment of the present invention, a hydrophilic modified microporous membrane is used as a reinforcing layer and composited with an ion exchange resin to prepare a composite ion exchange membrane. The hydrophilic polymer dispersion is spray-coated on the surface of the microporous membrane, thereby improving the hydrophilicity of the microporous membrane and the filling property of the ion exchange resin in the hydrophilic modified microporous membrane. The basic groups or phosphonic acid groups in the hydrophilic polymer can form ionic crosslinks with the acidic groups of the ion exchange resin, thereby improving the degree of bonding between the ion exchange resin and the hydrophilic modified microporous membrane interface, thereby achieving improvements in the electrochemical properties, mechanical properties, barrier properties and durability of the composite ion exchange membrane. When the composite ion exchange membrane is a proton exchange membrane, the improvement in the hydrophilicity of the microporous membrane can also improve the water retention of the proton exchange membrane, thereby broadening the operating temperature of the proton exchange membrane.
[0104] In some embodiments, the ion exchange resin is loaded on one side or both sides of the hydrophilic modified microporous membrane.
[0105] In some embodiments, the thickness of the composite ion exchange membrane is 3 μm to 500 μm, preferably 4 μm to 320 μm, more preferably 5 μm to 60 μm; the ion exchange capacity of the composite ion exchange membrane is 0.1 mmol / g to 5.2 mmol / g, preferably 0.15 mmol / g to 3.0 mmol / g, more preferably 0.2 mmol / g to 2 mmol / g.
[0106] In some embodiments, the ion exchange resin comprises at least one of perfluorosulfonic acid resin, perfluorosulfonimide resin, polyacid side chain perfluoro resin, sulfonated polytrifluorostyrene, sulfonated polysulfone, sulfonated polyethersulfone, sulfonated polyetheretherketone, sulfonated polyaryletherketone, sulfonated polyarylethernitrile, sulfonated polyphosphazene, sulfonated polyphenylene oxide, sulfonated polybenzonitrile, sulfonated polyimide or sulfonated polybenzimidazole; preferably, the ion exchange resin comprises at least one of perfluorosulfonic acid resin, perfluorosulfonimide resin, polyacid side chain perfluoro resin, sulfonated polytrifluorostyrene, sulfonated polyetheretherketone, sulfonated polyaryletherketone or sulfonated polyarylethernitrile; more preferably, the ion exchange resin comprises at least one of perfluorosulfonic acid resin, perfluorosulfonimide resin or polyacid side chain perfluoro resin.
[0107] In some embodiments, the general structural formula of the perfluorosulfonic acid resin is:
[0108]
[0109] In the formula, a=0-6, b=2-5, M" is selected from at least one of cations; x determines the ion exchange equivalent (EW) of the perfluorosulfonic acid resin, and y determines the molecular weight of the perfluorosulfonic acid resin.
[0110] In some embodiments, the general structural formula of the perfluorosulfonimide resin is:
[0111]
[0112] In the formula, a=0-6, b=2-5, c=0-5, M" is selected from at least one of cations; x' determines the EW of the perfluorosulfonyl imide resin, and y' determines the molecular weight of the perfluorosulfonyl imide resin.
[0113] In some embodiments, the general structural formula of the polyacid side chain perfluororesin is:
[0114]
[0115] In the formula, a=0-6, b=2-5, c=0-5, M" is selected from at least one of the cations, x" determines the EW of the polyacid side chain type perfluororesin, and y" determines the molecular weight of the polyacid side chain type perfluororesin.
[0116] In some embodiments, the cations include at least one of hydrogen ions, monovalent metal cations, ammonium ions, alkaline earth metal ions, manganese ions or cerium ions; optionally, the monovalent metal cations include at least one of lithium ions, sodium ions, potassium ions, and silver ions; the alkaline earth metal ions include at least one of magnesium ions and calcium ions.
[0117] A method for preparing a composite ion exchange membrane according to an embodiment of the present invention comprises the following steps:
[0118] 1) dispersing an ion exchange resin in a solvent to obtain an ion exchange resin dispersion;
[0119] 2) coating the ion exchange membrane resin dispersion on one side or both sides of the hydrophilic modified microporous membrane and drying to obtain a composite ion exchange membrane.
[0120] In the embodiment of the present invention, the preparation method of the composite ion exchange membrane can make the hydrophilic modified microporous membrane and the ion exchange resin have good bonding force to ensure better performance. The method of the present invention is simple and easy to operate, and is convenient for application in industrial production.
[0121] In some embodiments, in step 1), the ion exchange resin is dispersed in a solvent to obtain an ion exchange resin dispersion;
[0122] Optionally, the solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, tetramethyl sulfoxide, N-methylpyrrolidone, tetrahydrofuran, water, methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol; preferably, the solvent includes at least one of tetrahydrofuran, water, methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol; more preferably, the solvent includes at least one of water, ethanol, n-propanol, and isopropanol;
[0123] Optionally, the mass percentage concentration of the ion exchange resin dispersion is 0.01% to 60%, preferably 0.1% to 30%, and more preferably 0.1% to 25%.
[0124] In some embodiments, in step 2), the coating comprises at least one of dipping, blade coating, and slit coating.
[0125] In some embodiments, in step 2), the drying temperature is 40 to 200° C.; the drying time is 1 min to 24 h.
[0126] In some embodiments, in step 2), heat treatment is performed after drying; optionally, the temperature of the heat treatment is 100 to 220°C; and the time of the heat treatment is 1 to 120 minutes. In the embodiments of the present invention, the drying process can remove the solvent and regulate the physical structure of the polymer. Heat treatment after drying can further improve the physical structure of the composite ion exchange membrane. For example, perfluorosulfonic acid resin needs to be heat treated and crystallized above the glass transition temperature. Crystallization can improve the mechanical strength, chemical stability and solvent resistance of the ion exchange membrane.
[0127] The hydrophilic modified microporous membrane or composite ion exchange membrane of the embodiment of the present invention is used for at least one of filtration, separation, sealing material, and textile material. In the embodiment of the present invention, all the advantages of the hydrophilic modified microporous membrane or composite ion exchange membrane are possessed, which will not be described in detail here. The hydrophilic modified microporous membrane or composite ion exchange membrane has a wide range of applications.
[0128] In some embodiments, it is used for at least one of fuel cells, water electrolysis, flow batteries, chlor-alkali industry, electrodialysis or osmosis; preferably, it is used for fuel cell ion exchange membranes, ion exchange membranes for water electrolysis to produce hydrogen, flow battery diaphragms, chlor-alkali industry diaphragms, electrodialysis membranes or osmosis membranes. In the embodiments of the present invention, the composite ion exchange membrane has good durability when applied to fuel cell ion exchange membranes, ion exchange membranes for water electrolysis to produce hydrogen, and flow battery diaphragms. The composite ion exchange membrane can also be applied to chlor-alkali industry diaphragms, electrodialysis membranes, osmosis membranes and other fields, and has a wide range of applications.
[0129] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0130] The perfluorosulfonic acid resin or dispersion used in the embodiments of the present invention is from Chemours, 3M and Solvay. The polyacid side chain type perfluororesin is from 3M. The perfluorosulfonyl imide resin is obtained by copolymerizing tetrafluoroethylene and perfluorosulfonyl imide vinyl ether monomers.
[0131] Microporous membrane pore size test: The test method is the bubble pressure method (gas-liquid displacement technology), and the test instrument is the Porometer3G pore size analyzer. The wet-first-dry mode is adopted, that is, the microporous membrane is fully wetted with a liquid that can be infiltrated with it, and then a pressure difference is applied to both sides of the membrane to overcome the surface tension of the infiltrating liquid in the membrane pores, and the infiltrating liquid is driven through the pores to obtain the pore size distribution of the microporous membrane. The gas source is compressed air and nitrogen, and the test area is 3.14cm 2 . Take 3 to 5 groups of samples for parallel experiments each time.
[0132] Microporous membrane porosity test: The test equipment is a 0.01g high-precision balance and a true density analyzer; cut three square membranes of the same specifications and sizes without wrinkles, defects and damage as test samples. Use an analytical balance to weigh the mass of the three samples. Calculate the bulk density according to the following formula (1) as the apparent density of the sample:
[0133]
[0134] Where:
[0135] ρ—Volume density of the sample, in grams per cubic centimeter (g / cm 3 );
[0136] m—the mass measurement of the sample, in grams (g);
[0137] d—measured value of the thickness of the sample, in micrometers (μm);
[0138] S—sampling area of the sample, fixed as the sampling knife area, its value is 25cm 2 ;
[0139] The porosity is calculated according to the following formula (2):
[0140]
[0141] Where:
[0142] P—porosity of the sample, dimensionless physical quantity (%);
[0143] ρ—apparent density of the sample, which is the calculated value of the test, in grams per cubic centimeter (g / cm 3 );
[0144] ρ0—True density of the sample, in grams per cubic centimeter (g / cm 3 ), obtained by testing with a true density analyzer.
[0145] Contact angle test: The sessile drop method is used, the droplet is water, and the solid sample is a microporous membrane. The contact angle between the droplet and the microporous membrane is measured for 16 seconds. The smaller the contact angle, the better the hydrophilicity.
[0146] Microporous membrane thickness test: The test equipment is a contact flat-head thickness gauge. Use a cutter to cut three microporous membrane sheets as test samples. When measuring the thickness, take points equidistantly along the MD (longitudinal) and TD (transverse) directions of the sample for matrix testing, and calculate the average value of each point as the average thickness of the membrane.
[0147] Free radical resistance: The ion exchange membrane was immersed in Fenton's reagent at 80°C for 8 h, and the mass loss before and after different immersion times was compared. 2 O 2 0.1 mL of Fe with a molar concentration of 0.01 mol / L was added to the solution. 2+ The solution is the Fenton reagent, which is prepared and used immediately. The smaller the mass loss percentage, the better the durability.
[0148] The test methods for conductivity, EW, IEC and tensile strength refer to GB / T20042.3-2022 "Proton Exchange Membrane Fuel Cell Part 3: Proton Exchange Membrane Test Methods". Among them, the test conditions for conductivity are temperature 80°C and relative humidity 95%.
[0149] Fuel cell polarization curve and hydrogen permeation current: The test method refers to GB / T20042.5-2022 "Proton Exchange Membrane Fuel Cell Part 5: Membrane Electrode Test Method". The test conditions for the polarization curve are 80°C and 95% relative humidity. The test conditions for the hydrogen permeation current are 80°C and 80% relative humidity. The lower the hydrogen permeation current, the better the barrier property of the ion exchange membrane.
[0150] Barrier property: The barrier property of ion exchange membrane is characterized by oxygen permeability. The test and calculation method of oxygen permeability of ion exchange membrane is carried out according to the national standard GB1038-2000.
[0151] Example 1 Preparation of hydrophilic polymer dispersion and ion exchange resin dispersion
[0152] A certain amount of hydrophilic polymer or ion exchange resin is dissolved and dispersed in a solvent to obtain a dispersion. The polymer type, solvent composition and polymer mass content in the dispersion are shown in Table 1.
[0153] Table 1
[0154] Dispersion polymer Solvent composition (mass ratio) Polymer mass percentage Dispersion 1 PFNA-1 Ethanol 0.1% Dispersion 2 PFNA-2 Water:isopropyl alcohol=1:1 20% Dispersion 3 PFNA-3 Water: n-propanol: ethanol = 40:55:5 5% Dispersion 4 PEVOH-4 Water: ethanol = 1:3 10% Dispersion 5 PEVOH-5 Water: isopropanol: ethanol = 30:65:5 1% Dispersion 6 PFSA-6 Water: isopropanol = 1:2 20% Dispersion 7 PFSA-7 Water: n-propanol: ethanol = 1:2:1 10% Dispersion 8 PFSS-8 Water: n-propanol: tetrahydrofuran = 1:2:1 5% Dispersion 9 PFIA-9 Water: ethanol = 2:3 25%
[0155] PFNA-1, PFNA-2 and PFNA-3 are perfluoronitrogenium ion resins, PFVOH-4 and PEVOH-5 are phosphonated ethylene-vinyl alcohol copolymers, PFSA-6 and PFSA-7 are perfluorosulfonic acid resins, PFSS-8 is a perfluorosulfonyl imide resin, and PFIA-9 is a polyacid side chain resin.
[0156] The EW of PFNA-1 is 1035 g / mol, and the structural formula is:
[0157]
[0158] The EW of PFNA-2 is 910 g / mol, and the structural formula is:
[0159]
[0160] The EW of PFNA-3 is 821 g / mol, and the structural formula is:
[0161]
[0162] The EW value of PEVOH-4 is 153g / mol, and the structural formula is:
[0163]
[0164] The EW value of PEVOH-5 is 420g / mol, and the structural formula is:
[0165]
[0166] The EW of PFSA-6 is 980 g / mol, and the structural formula is:
[0167]
[0168] The EW of PFSA-7 is 720 g / mol, and the structural formula is:
[0169]
[0170] The EW of PFSS-8 is 1200 g / mol, and the structural formula is:
[0171]
[0172] The EW of PFIA-9 is 625 g / mol, and the structural formula is:
[0173]
[0174] Example 2 Preparation of MF-1A
[0175] Dispersion 1 was sprayed onto both sides of a polytetrafluoroethylene microporous membrane (e-PTFE-1) through an ultrasonic nozzle, dried at 40°C for 2 minutes, and treated at 150°C for 3 minutes to obtain a hydrophilic modified microporous membrane MF-1A. The frequency of the ultrasonic nozzle was 0.55 MHz, and the distance between the nozzle and the membrane surface was 20 cm.
[0176] Example 3 Preparation of MF-1B
[0177] Different from Example 2, the frequency of the ultrasonic nozzle is 1.3 MHz, and a hydrophilic modified microporous membrane MF-1B is obtained.
[0178] Example 4 Preparation of MF-1C
[0179] Different from Example 2, the frequency of the ultrasonic nozzle is 3 MHz, and a hydrophilic modified microporous membrane MF-1C is obtained.
[0180] Example 5 Preparation of MF-1D
[0181] Different from Example 2, the distance between the nozzle and the membrane surface is 80 cm, and a hydrophilic modified microporous membrane MF-1D is obtained.
[0182] Example 6 Preparation of MF-2
[0183] Dispersion 2 was coated on both sides of a polytetrafluoroethylene microporous membrane (e-PTFE-2) through an ultrasonic nozzle, dried at 80°C for 3 minutes, and treated at 160°C for 15 minutes to obtain a hydrophilic modified microporous membrane MF-2. The frequency of the ultrasonic nozzle was 1.3 MHz, and the distance between the nozzle and the membrane surface was 25 cm.
[0184] Example 7 Preparation of MF-3A
[0185] The dispersion 3 was coated on both sides of the polytetrafluoroethylene microporous membrane (e-PTFE-3) through an ultrasonic nozzle, dried at 60°C for 3 minutes, and treated at 150°C for 10 minutes to obtain a hydrophilic modified microporous membrane MF-3A. The frequency of the ultrasonic nozzle was 1.3 MHz, and the distance between the nozzle and the membrane surface was 20 cm.
[0186] Example 8 Preparation of MF-3B
[0187] The difference from Example 7 is that the hydrophilic polymer dispersion is the dispersion 4 in Example 1, and the hydrophilic modified microporous membrane MF-3B is obtained.
[0188] Example 9 Preparation of MF-3C
[0189] The difference from Example 7 is that the hydrophilic polymer dispersion is the dispersion 5 in Example 1, and the hydrophilic modified microporous membrane MF-3C is obtained.
[0190] Example 10 Preparation of MF-4
[0191] Different from Example 8, the skeleton material of the microporous membrane (ETFE-1) is ethylene-tetrafluoroethylene copolymer, and the hydrophilic modified microporous membrane MF-4 is obtained.
[0192] Example 11 Preparation of MF-5
[0193] Different from Example 7, the skeleton material of the microporous membrane (PE-1) is polyethylene, and a hydrophilic modified microporous membrane MF-5 is obtained.
[0194] Example 12 Preparation of MF-6
[0195] Different from Example 7, the skeleton material of the microporous membrane (PES-1) is polyethersulfone, and a hydrophilic modified microporous membrane MF-6 is obtained.
[0196] Example 13 Preparation of MF-7
[0197] Different from Example 7, the skeleton material of the microporous membrane (PVDF-1) is polyvinylidene fluoride, and a hydrophilic modified microporous membrane MF-7 is obtained.
[0198] Table 2 shows the skeleton polymer material, thickness, porosity and average pore size of the unmodified microporous membrane.
[0199] Table 2
[0200]
[0201] Table 3 shows the thickness of the hydrophilic modified microporous membrane, the mass content of the hydrophilic polymer, the porosity and the average pore size. The mass content of the hydrophilic polymer is the ratio of the mass of the hydrophilic polymer to the mass of the hydrophilic modified microporous membrane.
[0202] Table 3
[0203]
[0204]
[0205] As shown in Tables 2 and 3, the thickness, porosity and average pore size of the hydrophilic modified microporous membrane prepared by ultrasonic spraying change little. This is because the microporous membrane receives less solvent during the modification process and the pore structure does not undergo significant deformation. D-MF-1 is modified by using a scraper to coat ethanol. The microporous membrane is deformed under the action of a certain amount of ethanol solvent, and the thickness decreases, the porosity decreases, and the average pore size drops sharply. This drastic deformation is not conducive to its application in the ion exchange membrane reinforcement layer. D-MF-1E is modified by scraper coating with 0.1% PFSA-6 ethanol solution, and there is also a significant decrease in thickness, porosity and average pore size. Ultrasonic spray coating of microporous membranes to prepare hydrophilic modified microporous membranes can improve hydrophilicity while retaining the original structure of the microporous membrane to the greatest extent, which is beneficial to the processing and performance of ion exchange membranes. The preparation method of D-MF-1B is similar to that of MF-1B, and the thickness, porosity and average pore size of the microporous membrane are also similar to those of MF-1B.
[0206] Figure 1 The surface SEM images of MF-3A and e-PTFE-3. The hydrophilic polymer in MF-3 prepared by ultrasonic spraying is evenly dispersed and evenly coated on the surface of microporous membrane fibers. Compared with e-PTFE-3, the coated hydrophilic polymer can be observed at the fibers and nodes of MF-3A.
[0207] Figure 2 The contact angle images of hydrophilic modified microporous membrane and unmodified microporous membrane. The good hydrophilicity of the hydrophilic polymer improves the hydrophilicity of the microporous membrane surface. This improvement in hydrophilicity is conducive to the infiltration of ion exchange resin dispersion, reduces the processing difficulty of ion exchange membrane, and improves the filling property of ion exchange membrane resin.
[0208] Figure 3The contact angle images of MF-1B, D-MF-1B and D-MF-1E. The surface hydrophilicity of the microporous membrane was improved by surface modification of the microporous membrane with perfluoronitrogenium ion resin and perfluorosulfonic acid resin by spraying or coating. D-MF-1E has a higher content of perfluorosulfonic acid resin and has the smallest contact angle among the three. However, the thickness and pore size of D-MF-1E shrink severely, and the porosity decreases sharply compared with e-PTFE-1, and the composite effect with ion exchange resin is not good.
[0209] Example 14 Preparation of PEM-1B
[0210] The dispersion 7 in Example 1 was coated on both sides of the hydrophilic modified microporous membrane MF-1B by a doctor blade, dried at 80°C for 5 minutes, and heat treated at 150°C for 15 minutes to obtain an ion exchange membrane PEM-1B. The average thickness of PEM-1B was 12 μm, and the IEC was 1.20 mmol / g.
[0211] Example 15 Preparation of PEM-3A
[0212] The dispersion 6 in Example 1 was coated on both sides of the hydrophilic modified microporous membrane MF-3A by a doctor blade, dried at 90°C for 3 minutes, and heat treated at 160°C for 15 minutes to obtain an ion exchange membrane PEM-3A. The average thickness of PEM-3A was 25 μm, and the IEC was 0.82 mmol / g.
[0213] Example 16 Preparation of PEM-3B
[0214] The dispersion 9 in Example 1 was slit coated on both sides of the hydrophilic modified microporous membrane MF-3B, dried at 90°C for 3 minutes, and heat treated at 140°C for 5 minutes to obtain an ion exchange membrane PEM-3B. The average thickness of PEM-3B was 15 μm, and the IEC was 1.50 mmol / g.
[0215] Example 17 Preparation of PEM-6
[0216] The dispersion 8 in Example 1 was dip-coated on both sides of the hydrophilic modified microporous membrane MF-6, dried at 80°C for 5 minutes, and heat-treated at 150°C for 15 minutes to obtain an ion exchange membrane PEM-6. The average thickness of PEM-6 was 200 μm, and the IEC was 0.52 mmol / g.
[0217] Example 18 Preparation of PEM-4
[0218] The dispersion 6 in Example 1 was coated on both sides of the hydrophilic modified microporous membrane MF-4 by a doctor blade, dried at 80°C for 15 minutes, and heat treated at 150°C for 15 minutes to obtain an ion exchange membrane PEM-4. The average thickness of PEM-4 was 50 μm, and the IEC was 0.87 mmol / g.
[0219] Comparative Example 1
[0220] Ethanol was coated on both sides of the polytetrafluoroethylene microporous membrane (e-PTFE-1) by a doctor blade, dried at 40° C. for 2 min, and treated at 150° C. for 3 min to obtain the microporous membrane D-MF-1.
[0221] Comparative Example 2
[0222] The PFSA-6 ethanol solution was coated on both sides of the polytetrafluoroethylene microporous membrane (e-PTFE-1) by a doctor blade, dried at 40°C for 2 minutes, and treated at 150°C for 3 minutes to obtain the microporous membrane D-MF-1E. The mass content of the polymer in the PFSA-6 ethanol solution was 0.1%.
[0223] Comparative Example 3
[0224] Different from Example 3, the PFSA-6 ethanol solution in Comparative Example 2 was spray-coated on both sides of the polytetrafluoroethylene microporous membrane (e-PTFE-1) through an ultrasonic nozzle to obtain a microporous membrane D-MF-1B.
[0225] Comparative Example 4
[0226] The difference from Example 14 is that the reinforcement layer of the ion exchange membrane is the e-PTFE-1 in Example 2, and the ion exchange membrane D-PEM-1 is obtained. The average thickness of D-PEM-1 is 12 μm, and the IEC is 1.09 mmol / g.
[0227] Comparative Example 5
[0228] The difference from Example 14 is that the reinforcement layer of the ion exchange membrane is D-MF-1E in Comparative Example 2, and the ion exchange membrane D-PEM-1E is obtained. The average thickness of D-PEM-1E is 12 μm, and the IEC is 1.14 mmol / g.
[0229] Comparative Example 6
[0230] The difference from Example 14 is that the reinforcement layer of the ion exchange membrane is D-MF-1B in Comparative Example 3, and the ion exchange membrane D-PEM-1B is obtained. The average thickness of D-PEM-1B is 12 μm, and the IEC is 1.22 mmol / g.
[0231] Comparative Example 7
[0232] Different from Example 10, the dispersion 7 in Example 1 was spray-coated on both sides of the ethylene-tetrafluoroethylene copolymer microporous membrane (ETFE-1) through an ultrasonic nozzle to obtain a microporous membrane D-MF-4A.
[0233] Comparative Example 8
[0234] The difference from Example 16 is that the reinforcement layer of the ion exchange membrane is the e-PTFE-3 in Example 7, and the ion exchange membrane D-PEM-3 is obtained. The average thickness of D-PEM-3 is 15 μm, and the IEC is 1.45 mmol / g.
[0235] Comparative Example 9
[0236] Different from Example 18, the reinforcing layer of the ion exchange membrane is an unmodified microporous membrane ETFE-1, and the ion exchange membrane D-PEM-4 is obtained. The average thickness of D-PEM-4 is 50 μm, and the IEC is 0.93 mmol / g.
[0237] Comparative Example 10
[0238] The difference from Example 18 is that the reinforcement layer of the ion exchange membrane is D-MF-4A in Comparative Example 7, and the ion exchange membrane D-PEM-4A is obtained. The average thickness of D-PEM-4A is 50 μm, and the IEC is 0.95 mmol / g.
[0239] Table 4
[0240]
[0241] Table 4 shows the conductivity, tensile strength, free radical resistance and gas permeability of the composite ion exchange membrane. The smaller the percentage of free radical resistance mass loss, the better the durability of the ion exchange membrane. Compared with the ion exchange membrane prepared from the unmodified microporous membrane, the durability of the ion exchange membrane prepared from the hydrophilic modified microporous membrane is significantly improved. MF-1B contains only 0.16% of the hydrophilic polymer. Compared with D-PEM-1, PEM-1B has significantly improved free radical resistance, conductivity and mechanical properties. This is because the ion exchange resin has a better filling effect in the hydrophilic modified microporous membrane. Compared with D-PEM-1E, PEM-1B has a higher pore size and porosity of MF-1B, which is conducive to the filling of ion exchange resin. Although the hydrophilicity of both is improved, PEM-1B has better conductivity, tensile strength and free radical resistance. PEM-4 also has better comprehensive performance than D-PEM-4, indicating that the ultrasonic spray processing method can effectively improve the surface hydrophilicity of microporous membranes of different thicknesses and different skeleton polymer materials, thereby improving the application effect of microporous membranes in ion exchange membranes.
[0242] Compared with D-PEM-1B, PEM-1B has similar electrical conductivity, but the former has higher tensile strength and tensile modulus, less mass loss after Fenton reagent treatment and lower gas permeability. This is due to the ionic cross-linking effect formed by the basic nitrogen onium ion groups in the microporous membrane and the sulfonic acid groups in the ion exchange resin. This physical cross-linking effect can strengthen the bonding effect between the ion exchange resin and the microporous membrane, thereby improving the mechanical properties, chemical stability and barrier properties of the composite membrane material. Compared with PEM-4 and D-PEM-4A, the phosphonic acid groups in the former microporous membrane can not only play the role of proton transfer and proton compensation as acidic groups, but also can form ionic cross-linking structures as Lewis bases with the acidic groups of ion exchange resins. This cross-linking structure also improves the mechanical properties, chemical stability and barrier properties of the composite membrane material.
[0243] Figure 4 The cross-sectional SEM images of PEM-1B and D-PEM-1 show that the filling effect of ion exchange resin in PEM-1B is significantly better than that in D-PEM-1. This is because the surface hydrophilicity of the reinforcing layer MF-1B of PEM-1B is better, and there is an ion cross-linking effect between the reinforcing layer MF-1B and the ion exchange resin, so the ion exchange resin has a good infiltration effect and a high filling degree.
[0244] Figure 5 Polarization curves of PEM-1B, D-PEM-1 and D-PEM-1B. PEM-1B has better single cell performance and the power density reaches 1365mW / cm 2 @0.65V. The hydrogen permeation current of PME-1B is 2.2mA / cm 2 @0.4V, lower than 2.7mA / cm of D-PEM-1B 2 @0.4V and 3.9mA / cm for D-PEM-1 2 @0.4V, showing better barrier properties.
[0245] Figure 6 The efficiency of PEM-4 and D-PEM-4A flow batteries is 120 mA / cm for cycles 1-5, 6-10, 11-15, 16-20 and 21-25 respectively. 2 , 140mA / cm 2 , 160mA / cm 2 , 180mA / cm 2 and 200mA / cm 2 As the current density increases, the ohmic polarization phenomenon of the flow battery becomes more obvious, and the voltage efficiency and energy efficiency decrease. PEM-4 with a hydrophilic modified microporous membrane as the reinforcement layer as the flow battery separator shows better single cell performance at different current densities. The current density is 120mA / cm 2Under the same current density conditions, the coulombic efficiency is 97.3%, the voltage efficiency is 89.7%, and the energy efficiency is 86.4%. Under the same current density conditions, the coulombic efficiency of D-PEM-4A is 94.6%, the voltage efficiency is 88.7%, and the energy efficiency is 84.0%. The difference in coulombic efficiency between the two is the largest, because the coulombic efficiency is mainly affected by the membrane barrier. The ion cross-linking structure in PEM-4 makes it have better barrier properties, which improves the coulombic efficiency of the flow battery.
[0246] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0247] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A hydrophilic modified microporous membrane, characterized in that: The invention comprises a microporous membrane and a hydrophilic polymer, wherein the hydrophilic polymer is coated on one side or both sides of the microporous membrane by spraying, and the hydrophilic polymer comprises a cation exchange polymer and / or an anion exchange polymer.
2. The hydrophilic modified microporous membrane according to claim 1, characterized in that: The hydrophilic polymer comprises at least one of a nitrogen onium ion functionalized resin, a phosphonated vinyl polymer, a perfluorophosphonic acid resin, and a perfluorosulfonimide resin; and / or, the microporous membrane comprises at least one of a fluorine-containing olefin polymer, a non-fluorine-containing olefin polymer, and an aromatic polymer; and / or, the mass ratio of the microporous membrane to the hydrophilic polymer is 100:0.01-25; and / or, the thickness of the hydrophilic modified microporous membrane is 1 μm to 1 mm; and / or, the average pore size of the hydrophilic modified microporous membrane is 0.01 μm to 1 μm; And / or, the porosity of the hydrophilic modified microporous membrane is 30% to 95%.
3. A method for preparing a hydrophilic modified microporous membrane according to claim 1 or 2, characterized in that: The following steps are involved: (1) dispersing a hydrophilic polymer in a solvent to form a dispersion; (2) The dispersion is spray-coated on one or both sides of a microporous membrane, and then heat-treated to obtain a hydrophilically modified microporous membrane.
4. The method for preparing a hydrophilic modified microporous membrane according to claim 3, characterized in that: In the step (1), the mass percentage concentration of the dispersion is 0.01% to 60%; And / or, in step (2), the spray coating nozzle includes at least one of a pressure nozzle, a rotary nozzle, a two-phase flow nozzle, an ultrasonic nozzle, and an electrostatic nozzle; And / or, in step (2), the temperature of the heat treatment is room temperature to 300°C.
5. The method for preparing a hydrophilic modified microporous membrane according to claim 4, characterized in that: The spray coating adopts an ultrasonic nozzle; preferably, the frequency of the ultrasonic nozzle is 0.2MHz to 10MHz; and / or, the liquid transmission rate of a single nozzle of the spray coating is ≤50 mL / s; and / or, the average particle size of the atomized droplets of the spray coating is ≤50 μm; And / or, the spray coating has a spray distance of 1 cm to 150 cm.
6. A composite ion exchange membrane, characterized in that: The invention comprises an ion exchange resin and a hydrophilic modified microporous membrane, wherein the hydrophilic modified microporous membrane comprises the hydrophilic modified microporous membrane according to claim 1 or 2 or the hydrophilic modified microporous membrane prepared by the preparation method according to any one of claims 3 to 5.
7. The composite ion exchange membrane according to claim 6, characterized in that: The ion exchange resin is loaded on one side or both sides of the hydrophilic modified microporous membrane; And / or, the thickness of the composite ion exchange membrane is 3 μm to 500 μm; and / or, the ion exchange capacity of the composite ion exchange membrane is 0.1 mmol / g to 5.2 mmol / g; And / or, the ion exchange resin includes at least one of perfluorosulfonic acid resin, perfluorosulfonimide resin, polyacid side chain perfluoro resin, sulfonated polytrifluorostyrene, sulfonated polysulfone, sulfonated polyethersulfone, sulfonated polyetheretherketone, sulfonated polyaryletherketone, sulfonated polyarylethernitrile, sulfonated polyphosphazene, sulfonated polyphenylene oxide, sulfonated polybenzonitrile, sulfonated polyimide or sulfonated polybenzimidazole.
8. A method for preparing a composite ion exchange membrane according to claim 6 or 7, characterized in that: The following steps are involved: 1) dispersing an ion exchange resin in a solvent to obtain an ion exchange resin dispersion; 2) coating the ion exchange membrane resin dispersion on one side or both sides of the hydrophilic modified microporous membrane and drying to obtain a composite ion exchange membrane.
9. Use of the hydrophilic modified microporous membrane according to claim 1 or 2 or the composite ion exchange membrane according to claim 6 or 7, characterized in that: Used for at least one of filtering, separation, sealing material, and textile material.
10. The use according to claim 9, characterized in that: Used in at least one of fuel cells, water electrolysis, flow batteries, chlor-alkali industry, electrodialysis or osmosis.
Citation Information
Cited By
Separation membrane and preparation method thereof
CN121288574A
